SPE/IADC Middle East Drilling Technology Conference &Amp; Exhibition 2013
DOI: 10.2118/166698-ms
|View full text |Cite
|
Sign up to set email alerts
|

Neural-net Modeling of Shale-swelling Behavior in Aqueous Drilling Fluids

Abstract: Managing shale swelling is critical when drilling with water-based muds (WBMs). Excessive swelling can lead to shale sloughing, borehole collapse, stuck pipe, and shale disintegration. The fine solids content can increase and cause difficulties controlling rheological properties. Linear swell meter (LSM) testing is a well-known laboratory procedure used to characterize shale swelling in a WBMs.A mathematical modeling tool known as the artificial neural network (ANN) was used to model shale swelling in a WBM. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Similarly, Kulkarni et al 53 proposed a model to estimate the swelling of shale by including the shale's cation exchange capacity (CEC) and the concentrations of NaCl salt in the drilling fluid. Maghrabi et al 7 constructed an ANN model specifically for forecasting shale swelling in WBDFs. Their model aimed to capture the influence of shale mineralogy and fluid composition on shale swelling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Kulkarni et al 53 proposed a model to estimate the swelling of shale by including the shale's cation exchange capacity (CEC) and the concentrations of NaCl salt in the drilling fluid. Maghrabi et al 7 constructed an ANN model specifically for forecasting shale swelling in WBDFs. Their model aimed to capture the influence of shale mineralogy and fluid composition on shale swelling.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of extended reach wells is to access remote or hard-to-reach hydrocarbon reserves while minimizing the number of surface locations and drilling costs. , One of the significant challenges associated with extended reach wells is the risk of shale swelling when exposed to different water-based drilling fluids (WBDFs) . Shale swelling occurs when the shale formations encounter WBDFs, leading to the expansion and deformation of the shale rocks. Shale is composed of clay minerals, which can absorb water and expand. The interaction between shale and drilling fluids can have far-reaching consequences, including wellbore instability, formation damage, lost circulation, and decreased drilling efficiency. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to organic matter, shale also contains clay minerals, carbonate, and brittle minerals [21]. The clay content in shale is often an important factor affecting shale gas flow capacity, which is due to the swelling of clay when exposed to water [22][23][24][25]. The study of Pedlow and Sharma [23] indicated that the high clay content (over 20%) in shale can reduce the fracture conductivity in 3.5% salty water.…”
Section: Introductionmentioning
confidence: 99%